2016
DOI: 10.1016/j.jsg.2016.09.011
|View full text |Cite
|
Sign up to set email alerts
|

The role of gravitational collapse in controlling the evolution of crestal fault systems (Espírito Santo Basin, SE Brazil)

Abstract: A high-quality 3D seismic volume from offshore Espírito Santo Basin (SE Brazil) is used to assess the importance of gravitational collapse in the formation of crestal faults above salt structures. A crestal fault system is imaged in detail using seismic attributes such as curvature and variance, which are later complemented by analyses of throw vs. distance (T-D) and throw vs. depth (T-Z). In the study area, crestal faults comprise closely spaced arrays and are bounded by large listric faults, herein called bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 84 publications
(124 reference statements)
0
5
1
Order By: Relevance
“…Despite salt dissolution and the pressure exerted by overburden units on the Salt Ridge, no evidence of collapse as in Frumkin et al, (2011), Ge and Jackson, (1998) or Mattos et al, (2016), is observed in the 3D seismic volume for this same structure. This finding contrasts with observations for the eastern part of this seismic volume, where salt withdrawal and collapse play a major role in fault evolution (Alves et al, 2009;Ze and Alves, 2016). Throw-depth (T-z) data for the 12 representative faults, show that displacement decreases towards the Mid-Eocene horizon H6 (Fig.…”
Section: Structural Evolution Of the Salt Structures And Timing Of Facontrasting
confidence: 79%
See 2 more Smart Citations
“…Despite salt dissolution and the pressure exerted by overburden units on the Salt Ridge, no evidence of collapse as in Frumkin et al, (2011), Ge and Jackson, (1998) or Mattos et al, (2016), is observed in the 3D seismic volume for this same structure. This finding contrasts with observations for the eastern part of this seismic volume, where salt withdrawal and collapse play a major role in fault evolution (Alves et al, 2009;Ze and Alves, 2016). Throw-depth (T-z) data for the 12 representative faults, show that displacement decreases towards the Mid-Eocene horizon H6 (Fig.…”
Section: Structural Evolution Of the Salt Structures And Timing Of Facontrasting
confidence: 79%
“…The reasons for localised fault reactivation are also investigated and discussed in light of published work on different parts of the Espírito Santo Basin (e.g. Baudon and Cartwright, 2008;Omosanya and Alves, 2013;Ze and Alves, 2016). At the end of this paper, our results, and the integrated effects of halokinesis on the trapping and migration of fluids, are compared to areas with similar halokinetic structures.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Border faults were first identified in rift basins forming prominent fault escarpments on their shoulders; they have large displacements and lengths due to accommodating the bulk of strain and stress in extensional settings (Crossley and Crow, 1980;Ebinger et al, 1987). This structural control occurs at different scales of analysis; in the Espírito Santo Basin, SE Brazil, Ze and Alves (2016) proposed that fault families developed on the crest of salt structures were controlled by border faults, which have the largest maximum throws and accommodate most of the strain and stress on the crest of salt structures. Faults close to border faults are often less active, and are in a less preferential position to propagate and reactivate.…”
Section: Structural Inheritance Controlled By Basin-shoulder Faultsmentioning
confidence: 99%
“…Lindsay et al, 1993;Childs et al, 1997;Fristad et al, 1997;Fulljames et al, 1997;Knipe et al, 1997;Yielding et al, 1997Yielding et al, , 2010Yielding, 2002;Bretan et al, 2003;Faerseth et al, 2006). In general, these methodologies describe a capillary seal, where surface tension forces between the hydrocarbon and water prevent the hydrocarbon phase from entering the water-wet phase; hence, the volume of hydrocarbons that can be contained by the fault is controlled by the capillary entry pressure (Smith, 1980;Jennings, 1987;Watts, 1987). The capillary entry pressure depends on the hydrocarbon-water interface (specifically the wettability, interfacial tension and radius of the hydrocarbon), the difference between the hydrocarbon-phase and water-phase densities and the acceleration of gravity.…”
Section: Fault Seal Analysis: Capillary Sealmentioning
confidence: 99%